Biraderism At The Ballot: Clan, Caste, And Electoral Dynamics In District Narowal (2013-2018) - Dr. Imtiaz Ahmad; Saqib Ali; Tatheer Zahra, (Dialogue Social Science Review (DSSR), 2025)
The study analyzes how biraderism continues to influence electoral results in District Narowal during general elections in 2013 and 2018. A research design using mixed methods analyzes how birders' loyalties maintain dominance in political conduct despite socio-economic developments by merging primary questionnaires and interviews with secondary data sources. Data shows that dominant social groups, including the Jatt, Rajput, Gujjar, and Sayyad biraderis, utilised their caste affiliations as key factors in selecting candidates, organising voters, and achieving electoral victories. Land ownership, economic factors, and historical colonial structures strengthened biraderi-based political relationships, most notably in rural locations. Political mobilisation continued to be strongly guided by biraderism between the 2013 and 2018 vote periods, despite minor changes in voter behaviour emerging during this period. Although Pakistan has achieved democratic progression, the enduring strength of biraderism remains a hindrance to issue-based political development in the country's electoral system. The necessity of implementing policy solutions to advance democratic culture includes enhancing political party structures, teaching civil education nationwide, and developing birders-based alliances for inclusivity.